2008
DOI: 10.2174/156652308786070989
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Cationic Lipid-Mediated Gene Transfection: A Series of Bio- Inspired Lipids as an Example

Abstract: Over the last several years, various gene delivery systems have been developed for gene therapy applications. Although viral vector-based gene therapy has led to the greatest achievements in animal and human studies, synthetic non-viral vectors have also been developed as they offer several advantages over viral systems, including lower immunogenicity and greater nucleic acid packaging capacity. Nevertheless, the transfection efficiency of the current non-viral gene carriers still needs to be improved, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
110
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 0 publications
1
110
0
Order By: Relevance
“…26 Previous studies have reported that cationic liposomes can be used for gene delivery; they are easy to prepare, reasonably inexpensive, and can achieve ideal transfection. 27,28 Currently, the targeting liposome design is of great interest for the transport of genes into desired target cells; this method has the potential to produce greater and more selective therapeutic activity. This approach involves the coupling of targeting moieties capable of recognizing target cells, binding to them, and internalization of the liposomes and encapsulated gene.…”
Section: Discussionmentioning
confidence: 99%
“…26 Previous studies have reported that cationic liposomes can be used for gene delivery; they are easy to prepare, reasonably inexpensive, and can achieve ideal transfection. 27,28 Currently, the targeting liposome design is of great interest for the transport of genes into desired target cells; this method has the potential to produce greater and more selective therapeutic activity. This approach involves the coupling of targeting moieties capable of recognizing target cells, binding to them, and internalization of the liposomes and encapsulated gene.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, delivery systems for gene transfer are generally classified as viral and non-viral vectors. Non-viral vectors have many advantages over viral vectors, such as calcium phosphate, liposome, and emerging chitosan (38)(39)(40)(41)(42)(43). In our study, a novel nonviral gene delivery system was developed based on PEI.…”
Section: Discussionmentioning
confidence: 99%
“…[84] Depending on the chemical structure and the conditions for liposome preparation, these cationic lipids can be used to make cationic liposomes with or without additional lipids (helper lipids). A variety of positively charged lipid formulations are now commercially available and many others are under development (for reviews see Liu et al [85] and Montier et al [86] ).…”
Section: Liposome-based Nonviral Vectorsmentioning
confidence: 99%